THE INFLUENCE OF MANAGERIAL OWNERSHIP, INVESTMENT OPPORTUNITY SET, DEBT POLICY ON DIVIDEND POLICY WITH COMPANY SIZE AS A MODERATION (Study of Non-Financial Companies 2019-2021) - Cindy Valentina; I Gst Ayu Eka Damayanthi (Adisam Publisher, 2024)
A company's dividend policy is an important decision because it affects the company and its shareholders.Decision making regarding a company's dividend policy is a crucial aspect that affects both the company and its shareholders, especially in the context of the dynamics of the COVID-19 pandemic. The company always strives to improve performance to maximize shareholder benefits. However, managers as administrators often have goals that may be different, reflecting differences in interests between investors who expect dividends and management who may be more inclined to personal interests. The aim of this research is to determine the influence of managerial ownership, investment opportunity set, debt policy on dividend policy with company size as a moderator. The sample for this research is 68 non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. Sample selection in this research was carried out using a non-probability sampling approach using the purposive sampling method. The data analysis technique uses Moderated Regression Analysis (MRA). The research results show that managerial ownership, investment opportunity set, debt policy have a significant positive influence on dividend policy. Company size is able to strengthen the relationship between managerial ownership, investment opportunity set, and weaken the relationship between debt policy and dividend policy.